Kuru otlar üstüne = About dry grasses [videorecording (DVD)] - Ceylan, Nuri Bilge, 1959-; Ceylan, Nuri Bilge, 1959-; Aksu, Akın; Ceylan, Ebru, 1976-; Celiloğlu, Deniz; Dizdar, Merve; Ekici, Musab (Janus contemporaries., 2024)
The latest existential epic from Turkish director Nuri Bilge Ceylan is a masterclass in characterization, atmosphere, and moral and philosophical inquiry. When he comes under scrutiny for misconduct, cynical middle-school instructor Samet fears that his punishment will trap him in the snowy, isolated Anatolian village he has grown to despise. The only ray of hope is his relationship with Nuray, a fellow teacher who openly challenges Samet's bitter narcissism-yet Samet's friendship with his colleague and roommate, Kenan, who also has feelings for Nuray, hangs in the balance.